1992
DOI: 10.1530/jrf.0.0940451
|View full text |Cite
|
Sign up to set email alerts
|

Differential contribution of leucocytes and spermatozoa to the generation of reactive oxygen species in the ejaculates of oligozoospermic patients and fertile donors

Abstract: Summary. Cells isolated from the ejaculates of a high proportion of patients exhibiting oligozoospermia are characterized by generation rates of reactive oxygen species that considerably exceed those obtained for the normal fertile population. The purpose of this study was to resolve the cellular source of this enhanced activity. Semen samples from a cohort of oligozoospermic patients and a group of fertile controls were fractionated on discontinuous Percoll gradients to generate three cell populations (0, 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
118
1
8

Year Published

1994
1994
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(132 citation statements)
references
References 14 publications
5
118
1
8
Order By: Relevance
“…Low and medium concentrations of ROS are involved in cellular defense against infection agents, signal transduction, and response against mitogens, carboxylation, peroxidation, Pasqualotto et al [28] 0.03 ml [33] and reduction of ribonucleotides; however, high levels of ROS lead to various cellular damage [54][55][56][57][58][59]. ROS induced DNA damage involves base modifications, abasic sites, single strand (ss) and double strand (ds) DNA breaks, and DNA protein cross-links [60][61][62].…”
Section: Free Radical Theory Of Aging and Apoptosismentioning
confidence: 99%
“…Low and medium concentrations of ROS are involved in cellular defense against infection agents, signal transduction, and response against mitogens, carboxylation, peroxidation, Pasqualotto et al [28] 0.03 ml [33] and reduction of ribonucleotides; however, high levels of ROS lead to various cellular damage [54][55][56][57][58][59]. ROS induced DNA damage involves base modifications, abasic sites, single strand (ss) and double strand (ds) DNA breaks, and DNA protein cross-links [60][61][62].…”
Section: Free Radical Theory Of Aging and Apoptosismentioning
confidence: 99%
“…Although semen analysis indicated normal results, a number of abnormal spermatozoa or leukocytes could be identified in the sample. Those cells generated reactive oxygen species (ROS), which can penetrate through the sperm plasma membrane and initiate intrinsic ROS formation inside the spermatozoa, causing sperm damage, e.g., DNA fragmentation [12,[14][15][16][17][18][19]. After cryopreservation of spermatozoa, the percentage of abnormal spermatozoa in regards to motility, morphology, and DNA integrity significantly increases after freezing-thawing process [2,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In semen of fertile men, the amount of ROS is controlled by seminal antioxidants. The main sources of overproduction of ROS in the semen are leucocytes and morphologically abnormal spermatozoa [28]. Some authors demonstrated that high levels of ROS were detected in the semen of 25 to 40 % of infertile men [29].…”
Section: Discussionmentioning
confidence: 99%